A troupe performing Lezim - Mumbai Archive Project Team (Jio Institute, 2024)
A troupe performs lezim, a Maharashtrian folk dance known for its energetic and rhythmic movements, including jumps, spins, and coordinated group formations. The dance is named after the lezim, a musical instrument made of wooden or metal rods with small metallic discs attached. When shaken, the discs produce rhythmic jingling sounds.